VERIFIKASI cDNA T29 SEBAGAI KANDIDAT GEN PENGKODE PROTEIN Toxoplasma gondii DENGAN METODE SDS PAGE - Ira Djajanegara; Wayan Artama; Retno Lestari; Sabar Pambudi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2005)
The process of cDNA construction from mRNA isolated from Toxoplasma gondii has been done. There were 7 candidates cDNA which one of them is called T29. Since Toxoplasma gondii is the cause of toxoplasmosis infection, cloning the gene encoding protein from this parasite provides an important tool for developing diagnostic kit for detection of toxoplasmosis. Digestion of the cDNA T29 with EcoRI which is the restriction site where the cDNA was inserted yielded a 1.862 bp fragment. The fragment was subcloned into E. coli expression vector pMal-p2x and transformed into E.coli strain TB1. Colonies of TB1 were grown on ampicillin plates and the recombinant plasmid was extracted using the standard procedure. The plasmid was digested using EcoRI and PstI, checked by PCR amplification using malE and M13/pUC primers. The recombinant plasmid was expressed in TB1 and the protein extracted was ran in SDS PAGE to observe the presence of the expressed protein. Based on the data from this experiment, there was no expression result of the expressed cDNA which was confirm by the PCR result. Therefore, it was concluded that cDNA T29 was not carrying the gene coding for protein from parasite Toxoplasma gondii.